PENGARUH IMPLEMENTASI PRINSIP-PRINSIP GOOD GOVERNANCE TERHADAP KINERJA ORGANISASI (Suatu Studi Di Dinas Perindustrian Dan Perdagangan Kota Manado) - Setiadi, Adi; KIYAI, Burhanuddin; RURU, JOORIE MARHAEN (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract : This research moved from the problem that the performance of the Department ofIndustry and Trade organization Manado indicated relatively low. This is presumably related to theapplication of the principles of good governance do not optimal. Thus, this study aims to: (1). Todescribe the application / implementation of the principles of good governance. (2). To describealso the achievement of the organization's performance; and (3). To analyze the effect of theapplication / implementation of the principles of good governance to organizational performanceDepartment of Industry and Trade of Manado.By using a quantitative approach and descriptive method, data were collected throughquestionnaires distributed technique to 30 employees and 30 respondents respondents were fromindustry and commerce businesses. Once the data is collected, then processed and analyzed usingdescriptive analysis techniques stratisk (Table freuensi) to describe the variable-varabel research isconducted and to test the hypothesis applied inferential statistical analysis techniques (correlationand regression analysis).The results showed that (1) the application of the principles of participation, according to therespondents' assessment of employees are in the category of "moderate" tend to be high, while forthe group of businesses that are in the category of "moderate" or medium, tend to be low, but thetwo groups of respondents agree that the principle of participation has not been implementedoptimally, because only about 28.3% of all respondents (60 people) to assess the "high" applicationof the principles of good governance in the context of the application. (2) the application of theprinciples of transparency, responsiveness, rule of law and responsiveness, according to theassessment respondents the average employee in the category of "high", while the respondentbusinesses categorized only "moderate".Organizational performance through employee achievement in reality has not achieved optimally,even a group of businessmen assess the "low" while the employee group precisely assess the "high"the achievement of the organization's performance. However, the majority (36.7%) of the twogroups of respondents agree that the achievement of the organization's performance is still in thecategory of "low". This indicates that the achievement of performance at the organizational level ofthe Department of Industry and Trade of Manado has not been recorded in full so necessaryrearrangement.Thus, it can be concluded that the implementation of good governance and a real positive impacton organizational performance. This means that when the principles of good governance (goodgovernance) can be applied with no-Sunggu, it will encourage the improvement of organizationalperformance.Keywords: good governance, organizational performance.